Role of contextual and compositional characteristics of schools for health inequalities in childhood and adolescence: protocol for a scoping review - Matthias Richter; Nico Dragano; Irene Moor; Jennifer Hilger-Kolb; Stephanie Hoffmann; Max Herke; Claudia Pischke; Kristina Winter; Jacob Spallek; Anna Novelli (BMJ Open)
Introduction Childhood and adolescence are crucial life stages for health trajectories and the development of health inequalities in later life. The relevance of schools for health and well-being of children and adolescents has long been recognised, and there is some research regarding the association of contextual and compositional characteristics of schools and classes with health, health behaviour and well-being in this population. Little is known about the role of meso-level characteristics in relation to health inequalities. The aim of this scoping review is to retrieve and synthesise evidence about the mediating or moderating role of compositional or contextual characteristics of schools for the association between students’ socioeconomic position and health in primary and secondary education.Methods and analysis We will conduct a systematic search of electronic databases in PubMed/Medline, Web of Science and Education Resources Information Center. Studies must meet the following inclusion criteria: (1) The population must be students attending primary or secondary schools in developed economies. (2) The outcomes must include at least one indicator for individual health, health behaviour or well-being. (3) The study must include at least one contextual or compositional characteristic of the school context and one individual determinant of socioeconomic position. (4) The study must also examine the mediating or moderating role of the contextual or compositional characteristic of the school context for the associations between socioeconomic position and health, health behaviour or well-being. (5) The study must be published since 1 January 2000 in English or German language. We will provide a narrative synthesis of findings.Ethics and dissemination We will not collect primary data and only include secondary data derived from previously published studies. Therefore, ethical approval is not required. We intend to publish our findings in an international peer-reviewed journal and to present them at national and international conferences.